A Nb2O5 composite material and its preparation method and application
By using Nb2O5 composite material as the cathode material for magnesium-lithium hybrid batteries, the combination of porous carbon shell and Nb2O5 cores is solved, and the existing cathode material has low capacity, poor rate performance and limited cycle times are achieved, and high capacity and good cycle stability are achieved.
Patent Information
- Application Number
- CN202211047177.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-29
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-08-29
AI Technical Summary
The existing magnesium-lithium hybrid battery cathode materials have low capacity at low current density, poor rate performance, and limited cycle times, making it difficult to meet the needs of efficient energy storage and long life.
Nb2O5 composite material is used as the cathode material. This material consists of a porous carbon shell with a core of Nb2O5. Nb2O5 is coated with polyphosphazene-phenol nanomicrospheres, and a porous carbon shell co-doped by nitrogen, sulfur and phosphorus is formed by calcination.
The capacity and cycle stability of magnesium-lithium hybrid batteries are improved, and the capacity can exceed 200mAhg-1. After 2,200 cycles, the Coulon efficiency is still close to 100%, which significantly improves the battery performance.
Smart Images

Figure CN115207333B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of inorganic nanomaterials and electrochemistry, and specifically relates to a Nb 2 O 5 Composite material and preparation method and application thereof. Background Art
[0002] Magnesium-lithium hybrid batteries directly use magnesium metal / alloy as the negative electrode, combined with Li with high capacitance / high voltage + or Mg 2+ Intercalation / conversion materials are used as positive electrodes, assisted by Mg 2+ and Li + The dual-ion organic liquid is the electrolyte. Since magnesium-lithium hybrid batteries can combine the advantages of high capacitance / high voltage positive electrode, faster positive ion embedding speed of lithium-ion batteries and high capacitance / less dendrite magnesium metal negative electrode in magnesium batteries, they have attracted great attention.
[0003] At present, there is a wide range of options for positive electrode materials for magnesium-lithium hybrid batteries. They can be typical lithium battery positive electrode materials, magnesium battery positive electrode materials, or both common positive electrode materials, such as LiFePO 4 , Prussian blue, Mo 6 S 8 , Li 4 Ti 5 O 12 However, they still fail to solve the problems of low capacity, poor rate performance and poor cycle stability. For example, when these materials are used as positive electrodes, the current density is low (0.01-0.02Ag -1 ) and its capacity does not exceed 200mAhg -1 , the rate performance is poor and the number of cycles does not exceed 200 times. Summary of the invention
[0004] The present invention aims to provide a Nb 2 O 5 Composite material and preparation method and application thereof, with Nb 2 O 5 Magnesium-lithium hybrid batteries with composite materials as positive electrodes have high capacity and good cycle stability.
[0005] The present invention provides a Nb 2 O 5 Composite material, comprising a core and a shell, wherein the core is Nb 2 O 5 , the shell is porous carbon co-doped with nitrogen, sulfur and phosphorus.
[0006] Preferably, the porous carbon has a pore size of less than 100 nm and a specific surface area of 5 to 200 m 2 / g, pore volume is 0.01~0.1cm 3 / g; the thickness of the shell is 10 to 50 nm.
[0007] Preferably, the Nb 2 O 5 Orthorhombic Nb 2 O 5 .
[0008] Preferably, the Nb 2 O 5 The particle size of the composite material is 5 to 550 nm.
[0009] The present invention also provides the Nb 2 O 5 The method for preparing the composite material comprises the following steps:
[0010] The organic solution containing hexachlorocyclotriphosphazene and 4,4'-sulfonyldiphenol and Nb 2 O 5 to obtain a mixture;
[0011] The mixture is mixed with trialkylamine to carry out polymerization reaction, and the hexachlorocyclotriphosphazene is polymerized with 4,4'-sulfonyldiphenol to be coated on Nb 2 O 5 surface, and Nb 2 O 5 Polyphosphazene-phenol nanoparticles;
[0012] The coated Nb 2 O 5 The polyphosphazene-phenol nanospheres were calcined and carbonized in an inert gas. 2 O 5 The porous carbon co-doped with nitrogen, sulfur and phosphorus is formed on the surface to obtain the Nb 2 O 5 Composite materials.
[0013] Preferably, in the mixture, hexachlorocyclotriphosphazene, 4,4'-sulfonyldiphenol and Nb 2 O 5 The mass ratio is 250-350:500-700:200-1000.
[0014] Preferably, the Nb 2 O 5 The concentration of the dispersion is 0.5~5Kg / m 3 .
[0015] Preferably, the calcination includes sequentially performing a first calcination, heating and a second calcination; the temperature of the first calcination is 200-500°C, and the insulation time is 0.5-2h; the temperature of the second calcination is 500-900°C, and the insulation time is 2-4h.
[0016] Preferably, the trialkylamine includes triethylamine; and the mass ratio of the trialkylamine to hexachlorocyclotriphosphazene is 1:250-1000.
[0017] The present invention also provides the Nb 2 O 5 Composite material or Nb prepared by the preparation method described in the above scheme 2 O 5 Application of composite materials as positive electrode materials in magnesium-lithium hybrid batteries.
[0018] The present invention provides a Nb 2 O 5 Composite material, comprising a core and a shell, wherein the core is Nb 2 O 5 The shell is porous carbon co-doped with nitrogen, sulfur and phosphorus. 2 O 5 The composite material combines Nb 2 O 5 High pseudocapacitive performance and advantages of high conductivity, high porosity and multiple energy storage sites of doped porous carbon: Nb 2 O 5 It has high pseudocapacitive performance in magnesium-lithium mixed electrolyte; the pores of porous carbon can realize Nb 2 O 5 Contact with positive ions (magnesium ions and lithium ions) in the electrolyte, accommodating the penetration of positive ions, increasing the Nb 2 O 5 The capacity of the composite material as the positive electrode material of magnesium-lithium hybrid battery; and the nitrogen, sulfur and phosphorus co-doped porous carbon can provide lithium or magnesium ion storage sites, further increasing the Nb 2 O 5 The capacitance of the composite material; In addition, Nb 2 O 5 The core-shell structure of the composite material and the porous structure in the shell make Nb 2 O 5 The damage caused by volume change during the charge and discharge process is avoided, and the cycle stability is improved. 2 O 5 The capacity of magnesium-lithium hybrid batteries with composite materials as positive electrodes can exceed 200 mAhg -1 , and after 2200 cycles, the Coulombic efficiency is still close to 100%. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The Nb prepared in Example 3 2 O 5 Low magnification SEM image of the composite material;
[0020] Figure 2 The Nb prepared in Example 3 2 O 5 High magnification SEM image of the composite material;
[0021] Figure 3 The Nb prepared in Example 3 2 O 5 Nitrogen desorption and adsorption diagram of the composite material;
[0022] Figure 4 The Nb prepared in Example 3 2 O 5 The pore size distribution diagram corresponding to the nitrogen adsorption-desorption curve of the composite material;
[0023] Figure 5 The Nb prepared in Example 3 2 O 5 Transmission electron microscopy images of composite electrode materials;
[0024] Figure 6 The Nb prepared in Example 3 2 O 5 High-magnification transmission electron microscopy image of the composite electrode material;
[0025] Figure 7 This is the cyclic voltammogram of the magnesium-lithium hybrid battery of Application Example 1;
[0026] Figure 8 This is a constant current charge and discharge diagram of a magnesium-lithium hybrid battery in Application Example 1;
[0027] Fig. 9 This is the cycle curve of the magnesium-lithium hybrid battery of Application Example 1 at a current density of 2A / g.
[0028] Fig.10 It is the cycle curve of the magnesium-lithium hybrid battery of comparative application example 1 at different current densities. DETAILED DESCRIPTION
[0029] The present invention provides a Nb 2 O 5 Composite material, comprising a core and a shell, wherein the core is Nb 2 O 5 , the shell is porous carbon co-doped with nitrogen, sulfur and phosphorus.
[0030] In the present invention, the pore size of the porous carbon is preferably less than 100 nm, more preferably 20 to 80 nm, and further preferably 40 to 60 nm; the specific surface area is preferably 5 to 200 m 2 / g, more preferably 50 to 150 m 2 / g, more preferably 100 to 120 m 2 / g; the pore volume is preferably 0.01 to 0.1 cm 3 / g, more preferably 0.049 to 0.5 cm 3 / g, more preferably 0.1 to 0.3 cm 3 / g. The thickness of the shell is preferably 10 to 50 nm, more preferably 20 to 45 nm, and further preferably 30 to 40 nm. In the present invention, the Nb 2 O 5 Preferably, orthorhombic Nb 2 O 5 In the present invention, the Nb 2 O 5 The particle size of the composite material is preferably 5 to 550 nm, more preferably 20 to 400 nm, and even more preferably 50 to 300 nm.
[0031] The Nb of the present invention 2 O 5 The composite material has both porous carbon and Nb 2 O 5 Both have high capacitance and excellent cycle stability. The pores of porous carbon can realize Nb 2 O 5 Contact with positive ions (magnesium ions and lithium ions) in the electrolyte, accommodating the penetration of positive ions, increasing the Nb 2 O 5 The capacity of the composite material as the positive electrode material of magnesium-lithium hybrid battery; and the nitrogen, sulfur and phosphorus co-doped porous carbon can provide lithium or magnesium ion storage sites, further improving the Nb 2 O 5 The capacitance of the composite material; In addition, Nb 2 O 5 The core-shell structure and high specific surface area of the composite material make Nb 2 O 5 The damage caused by volume change during the charge and discharge process is avoided, and the cycle stability is improved.
[0032] The present invention also provides the Nb 2 O 5 The method for preparing the composite material comprises the following steps:
[0033] The organic solution containing hexachlorocyclotriphosphazene and 4,4'-sulfonyldiphenol and Nb2 O 5 to obtain a mixture;
[0034] The mixture is mixed with trialkylamine to carry out polymerization reaction, and the hexachlorocyclotriphosphazene is polymerized with 4,4'-sulfonyldiphenol to be coated on Nb 2 O 5 surface, and Nb 2 O 5 Polyphosphazene-phenol nanoparticles;
[0035] The coated Nb 2 O 5 The polyphosphazene-phenol nanospheres were calcined in an inert gas atmosphere. 2 O 5 The porous carbon co-doped with nitrogen, sulfur and phosphorus is formed on the surface to obtain the Nb 2 O 5 Composite materials.
[0036] The present invention comprises an organic solution containing hexachlorocyclotriphosphazene and 4,4'-sulfonyldiphenol and Nb 2 O 5 and mixing the dispersions to obtain a mixture.
[0037] In the present invention, the method for preparing the organic solution containing hexachlorocyclotriphosphazene and 4,4'-sulfonyl diphenol preferably comprises: dissolving hexachlorocyclotriphosphazene and 4,4'-sulfonyl diphenol in an organic solvent (such as methanol, acetonitrile, etc.) to obtain the organic solution containing hexachlorocyclotriphosphazene and 4,4'-sulfonyl diphenol. In the present invention, the mass concentration of hexachlorocyclotriphosphazene in the organic solvent is preferably 5 to 20 mg / mL, more preferably 8 to 15 mg / mL, and further preferably 10 to 12 mg / mL. The present invention has no special limitation on the dissolution method, and the solution can be completely dissolved using a scheme familiar to those skilled in the art. In the present invention, the Nb 2 O 5 The method for preparing the dispersion preferably comprises: 2 O 5 Dispersed in an organic solvent to obtain the Nb 2 O 5 In the present invention, the Nb 2 O 5 The concentration of the dispersion is preferably 0.5 to 5 kg / m 3 , more preferably 1 to 4.5 Kg / m 3 , more preferably 2 to 3 kg / m 3The present invention has no special limitation on the dispersion method, and a method known to those skilled in the art can be used to disperse uniformly. Specifically, in the embodiment of the present invention, magnetic stirring is used. In the present invention, the organic solvent used to dissolve hexachlorocyclotriphosphazene and 4,4'-sulfonyldiphenol is the same as the organic solvent used to disperse Nb 2 O 5 The organic solvent used is preferably the same, and the organic solvent preferably comprises methanol or acetonitrile.
[0038] In the present invention, in the mixture, hexachlorocyclotriphosphazene, 4,4'-sulfonyldiphenol and Nb 2 O 5 The mass ratio of Nb is preferably 250-350:500-700:200-1000, more preferably 280-320:550-650:400-800, and further preferably 300:650:600. 2 O 5 The dispersion is added dropwise to an organic solution containing hexachlorocyclotriphosphazene and 4,4'-sulfonyldiphenol. The addition is preferably carried out under stirring. After the addition is completed, the stirring is preferably continued for 5 to 60 minutes, more preferably 20 to 50 minutes, and further preferably 30 to 40 minutes. The stirring speed is preferably 300 rpm.
[0039] After obtaining the mixture, the present invention mixes the mixture with trialkylamine to carry out polymerization reaction, and the hexachlorocyclotriphosphazene and 4,4'-sulfonyl diphenol are polymerized and coated on Nb 2 O 5 surface, and Nb 2 O 5 Polyphosphazene-phenol nanospheres. In the present invention, the mass ratio of the trialkylamine to hexachlorocyclotriphosphazene is preferably 1:250-1000, more preferably 1:500-800, and further preferably 1:600-700; the trialkylamine preferably includes triethylamine. When the mixture is mixed with the trialkylamine in the present invention, the trialkylamine is preferably added dropwise to the mixture. The dropping rate is preferably 10 mL / h. The polymerization reaction time of the present invention is preferably 5-10 h, more preferably 6-8 h. The polymerization reaction is preferably carried out under stirring, and the stirring rate is preferably 300 rpm. In the polymerization reaction, hexachlorocyclotriphosphazene (HCCP) and 4,4'-sulfonyldiphenol (BPS) undergo polymerization to generate polyphosphazene-phenol coated on Nb 2 O 5 The surface forms a core-shell structure of Nb 2 O 5 Polyphosphazene-phenol nanospheres. Taking trialkylamine as triethylamine (TEA) as an example, the reaction mechanism is:
[0040]
[0041] After the polymerization reaction, the present invention preferably centrifuges, washes and dries the obtained polymerization product to obtain coated Nb 2 O 5 The present invention has no special limitation on the centrifugation, and a method well known to those skilled in the art can be used. The washing is preferably performed with water and ethanol. The reactant of the trialkylamine is removed during the washing process. The present invention has no special limitation on the number and method of washing, and a method well known to those skilled in the art can be used to clean the unreacted raw materials. The drying is preferably performed in a vacuum oven.
[0042] Get coated Nb 2 O 5 After the polyphosphazene-phenol nanospheres are prepared, the present invention coats the Nb 2 O 5 The polyphosphazene-phenol nanospheres were calcined in an inert gas atmosphere. 2 O 5 The porous carbon co-doped with nitrogen, sulfur and phosphorus is formed on the surface to obtain the Nb 2 O 5 Composite material. In the present invention, the calcination preferably includes a first calcination, a heating and a second calcination in sequence; the temperature of the first calcination is preferably 200-500°C, more preferably 300-400°C, and the holding time is preferably 0.5-2h, more preferably 1-1.5h; the temperature of the second calcination is 500-900°C, and the holding time is preferably 2-4h, more preferably 2.5-3h. The heating rate is preferably 2-8, preferably 5-6°C / min. In the present invention, the calcination is preferably carried out under an argon atmosphere. In the calcination process of the present invention, the coated Nb with a core-shell structure 2 O 5 The polyphosphazene-phenol in the polyphosphazene-phenol nanospheres undergoes a carbonization reaction during the calcination process, and the nitrogen, phosphorus and sulfur elements in the polyphosphazene-phenol are doped into the generated carbon, and the carbon becomes porous carbon due to the sublimation of small molecules in the "shell". After calcination, the present invention preferably cools the calcined product naturally to room temperature to obtain the Nb 2 O 5 Composite materials.
[0043] The present invention also provides the Nb 2 O 5 Composite material or Nb prepared by the preparation method described in the above scheme 2 O 5The present invention has no special limitation on the application, and conventional technical solutions can be used. Specifically, in the embodiment of the present invention: Nb 2 O 5 The composite material is mixed with the conductive agent and polytetrafluoroethylene in a mass ratio of 8:1:1 and evenly coated on a stainless steel mesh to form a positive electrode. The magnesium-lithium hybrid battery uses a magnesium sheet electrode as a negative electrode and a tetrahydrofuran solution (THF) of aluminum chloride-stabilized phenylmagnesium chloride + lithium chloride as an electrolyte.
[0044] In order to further illustrate the present invention, the following is a Nb provided by the present invention in conjunction with the accompanying drawings and embodiments. 2 O 5 The composite material and its preparation method and application are described in detail, but they should not be understood as limiting the scope of protection of the present invention.
[0045] Example 1
[0046] Take 0.2g Nb 2 O 5 Dispersed in 200 mL of methanol solution, stirred at 300 rpm for 0.5 h, Nb 2 O 5 dispersion;
[0047] 0.2 g of hexachlorocyclotriphosphazene and 0.5 g of 4,4'-sulfonyldiphenol were dissolved in 20 mL of methanol by magnetic stirring to obtain an organic solution containing hexachlorocyclotriphosphazene and 4,4'-sulfonyldiphenol;
[0048] Nb 2 O 5 The dispersion is added dropwise into an organic solution containing hexachlorocyclotriphosphazene and 4,4'-sulfonyldiphenol and stirred for 5 minutes to obtain a mixture;
[0049] 1 mL of triethylamine was added dropwise to the mixture at a rate of 10 mL / h, and the polymerization reaction was carried out for 6 h under stirring. The polymerization product was centrifuged, washed with ethanol and deionized water, and then dried in a vacuum oven to obtain coated Nb 2 O 5 Polyphosphazene-phenol nanoparticles;
[0050] Coating Nb 2 O 5 The polyphosphazene-phenol nanospheres were first calcined at a rate of 5°C / min to 300°C and kept at that temperature for 1h, and then the temperature was raised to 700°C at a rate of 5°C / min and kept at that temperature for 3h for the second calcination. The calcined product was cooled to room temperature and then taken out to obtain Nb 2 O 5 Composite materials.
[0051] The obtained Nb 2 O 5 The composite material has good particle dispersion and its particle size is 50-200nm. 2 O 5 The thickness of the outer shell in the composite material is 50 nm, and the outer shell is porous carbon co-doped with nitrogen, sulfur and phosphorus.
[0052] Example 2
[0053] The rest is the same as Example 1, except that 0.4 g of Nb 2 O 5 Place in 200mL methanol solution. 2 O 5 The thickness of the outer shell in the composite material is 40 nm, and the outer shell is porous carbon co-doped with nitrogen, sulfur and phosphorus.
[0054] Example 3
[0055] The rest is the same as Example 1, except that 0.6 g of Nb 2 O 5 Place in 200 mL of methanol solution.
[0056] The Nb prepared in Example 3 2 O 5 The composite material was subjected to SEM analysis at different magnifications. Figure 1 and Figure 2 As shown. Figure 1 and Figure 2 It can be seen that Nb in Example 3 2 O 5 The composite material particles have good dispersibility and a particle size of 50 to 200 nm. 2 O 5 The composite material was subjected to nitrogen desorption and adsorption experiments. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the curve has a hysteresis loop, indicating that Nb 2 O 5 The composite material has a pore structure. Figure 3 It can be obtained that Nb in Example 3 2 O 5 The specific surface area of the composite material is 32m 2 / g, pore volume is 0.049cm 3 / g
[0057] The Nb prepared in Example 3 2 O 5 The composite material was subjected to pore size analysis, and the results were as follows Figure 4 As shown by Figure 4It can be seen that the pore size of the obtained samples is concentrated at 1.9 nm, and there is also a pore size distribution between 10 and 50 nm.
[0058] The Nb prepared in Example 3 2 O 5 The composite material was analyzed by transmission electron microscopy. Figure 5 As shown. Figure 5 It can be seen that the thickness of the outer shell in the Nb2O5 composite material of Example 3 is 30 nm.
[0059] The Nb prepared in Example 3 2 O 5 The composite material was analyzed by high-power transmission electron microscopy. Figure 6 As shown. Figure 6 It can be seen that the spacing of the (001) crystal plane is 0.39nm, indicating that the obtained composite structure does not destroy the cubic Nb 2 O 5 of the crystal structure.
[0060] Example 4
[0061] The rest is the same as Example 1, except that 0.8 g of Nb 2 O 5 Place in 200mL methanol solution. 2 O 5 The thickness of the shell in the composite material is 20 nm, and the shell is porous carbon co-doped with nitrogen, sulfur and phosphorus.
[0062] Example 5
[0063] The rest is the same as Example 1, except that 1.0 g of Nb 2 O 5 Place in 200mL methanol solution. 2 O 5 The thickness of the shell in the composite material is 10 nm, and the shell is porous carbon co-doped with nitrogen, sulfur and phosphorus.
[0064] Comparative Example 1
[0065] The other aspects are the same as in Example 1 except that Nb is not added. 2 O 5 .
[0066] Comparative Example 2
[0067] 0.2gNb 2 O 5Mix with 5mL of 1M glucose aqueous solution, and then add 20mL of deionized water to form a uniform mixture. After half an hour, add the above solution into a 45mL polytetrafluoroethylene-lined autoclave, seal it tightly, and heat it in a furnace at 180°C for 4 hours. Then, separate the sample by centrifugation, wash the sample with water 3 times, and then dry it in an oven at 60°C for 12 hours. Then, load the dried sample into a tubular furnace, heat it at 700°C under an argon atmosphere for 3 hours, and the heating rate is 1°C / min. Finally, porous carbon-wrapped Nb 2 O 5 Composite materials.
[0068] Application Example 1
[0069] 1 mg Nb prepared in Example 3 2 O 5 The composite material was mixed with a conductive agent (acetylene black) and polytetrafluoroethylene (PTFE) (binder) in a mass ratio of 8:1:1 and evenly coated on a circular stainless steel mesh with a radius of 6 mm, a thickness of 0.05 mm and a mesh size of 200 to make a positive electrode. A square magnesium sheet with a length of 10 mm and a thickness of 0.1 mm was used as a negative electrode. A tetrahydrofuran solution (THF) of aluminum chloride-stabilized phenylmagnesium chloride (0.4MAPC) + lithium chloride (0.4MLiCl) was used as a magnesium-lithium dual ion electrolyte (APC-LiCl electrolyte) to make a magnesium-lithium hybrid battery for testing the electrochemical performance.
[0070] The above magnesium-lithium hybrid battery was subjected to cyclic voltammetry test, and the results are as follows: Figure 7 As shown. Figure 7 It can be seen that magnesium-lithium hybrid batteries have good charge and discharge reversibility.
[0071] The above magnesium-lithium hybrid battery was subjected to constant current charge and discharge test, and the results are as follows Figure 8 As shown. Figure 8 It can be seen that the capacitance of magnesium-lithium hybrid battery reaches 206mAh / g.
[0072] The above magnesium-lithium hybrid battery was subjected to constant current charge and discharge test at a current density of 2A / g. The results are as follows Fig. 9 As shown. Fig. 9 It can be seen that the magnesium-lithium hybrid battery still has good retention after 2200 cycles, showing good and cycle-stable electrochemical performance.
[0073] Comparative application example 1
[0074] The difference from Application Example 1 is that the Nb 2 O 5 The prepared magnesium-lithium hybrid battery was subjected to constant current charge and discharge tests at different current densities, and the results are shown in FIG10 . Fig.10 It can be seen that even if Nb 2 O 5 When the proportion in the composite material is low, its discharge specific capacitance is only 182 mAh / g at 0.1 A / g.
[0075] Comparative Example 2
[0076] The difference from Application Example 1 is that the Nb 2 O 5 The composite material is used to prepare a magnesium-lithium hybrid battery. The prepared magnesium-lithium hybrid battery is subjected to constant current charge and discharge tests at different current densities, and its discharge specific capacitance is only 150mAh / g at 0.1A / g.
[0077] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. Application of Nb2O5 composite material as positive electrode material in magnesium-lithium hybrid battery, characterized in that: The Nb2O5 composite material comprises a core and an outer shell, wherein the core is Nb2O5 and the outer shell is porous carbon co-doped with nitrogen, sulfur and phosphorus; The Nb2O5 is orthorhombic phase Nb2O5; The preparation method of the Nb2O5 composite material comprises the following steps: mixing an organic solution containing hexachlorocyclotriphosphazene and 4,4'-sulfonyldiphenol and a dispersion of Nb2O5 to obtain a mixture; The mixture is mixed with trialkylamine to carry out a polymerization reaction, and the hexachlorocyclotriphosphazene and 4,4'-sulfonyldiphenol are polymerized and coated on the surface of Nb2O5 to obtain polyphosphazene-phenol nanoparticles coated with Nb2O5; The polyphosphazene-phenol nano-microspheres coated with Nb2O5 are calcined and carbonized in an inert gas to form porous carbon co-doped with nitrogen, sulfur and phosphorus on the surface of Nb2O5, thereby obtaining the Nb2O5 composite material.
2. The use according to claim 1, characterized in that: The porous carbon has a pore size of less than 100 nm and a specific surface area of 5 to 200 m 2 / g, pore volume is 0.01~0.1cm 3 / g; the thickness of the shell is 10 to 50 nm.
3. The use according to claim 1 or 2, characterized in that: The particle size of the Nb2O5 composite material is 5 to 550 nm.
4. The use according to claim 1, characterized in that: In the mixture, the mass ratio of hexachlorocyclotriphosphazene, 4,4'-sulfonyldiphenol and Nb2O5 is 250-350:500-700:200-1000.
5. The use according to claim 1, characterized in that: The concentration of the Nb2O5 dispersion is 0.5-5 Kg / m 3 .
6. The use according to claim 1, characterized in that: The calcination includes sequentially performing a first calcination, heating and a second calcination; the temperature of the first calcination is 200-500° C., and the insulation time is 0.5-2 hours; the temperature of the second calcination is 500-900° C., and the insulation time is 2-4 hours.
7. The use according to claim 1, characterized in that: The trialkylamine includes triethylamine; the mass ratio of the trialkylamine to hexachlorocyclotriphosphazene is 1:250-1000.
Citation Information
Patent Citations
Preparation method of molybdenum disulfide composite carbon composite electrode material with polyphosphazene as carbon source
CN107248573A
Composite material, and preparation method and application thereof
CN112928246A